Interaction of Severe Acute Respiratory Syndrome Coronavirus 2 and Diabetes - Shao, Shiying; Yang, Qin; Pan, Ruping; Yu, Xuefeng; Chen, Yong (Frontiers in Endocrinology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is causing a worldwide epidemic. It spreads very fast and hits people of all ages, especially patients with underlying diseases such as diabetes. In this review, we focus on the influences of diabetes on the outcome of SARS-CoV-2 infection and the involved mechanisms including lung dysfunction, immune disorder, abnormal expression of angiotensin-converting enzyme 2 (ACE2), overactivation of mechanistic target of rapamycin (mTOR) signaling pathway, and increased furin level. On the other hand, SARS-CoV-2 may trigger the development of diabetes. It causes the damage of pancreatic β cells, which is probably mediated by ACE2 protein in the islets. Furthermore, SARS-CoV-2 may aggravate insulin resistance through attacking other metabolic organs. Of note, certain anti-diabetic drugs (OADs), such as peroxisome proliferator-activated receptor γ (PPARγ) activator and glucagon-like peptide 1 receptor (GLP-1R) agonist, have been shown to upregulate ACE2 in animal models, which may increase the risk of SARS-CoV-2 infection. However, Metformin, as a first-line medicine for the treatment of type 2 diabetes mellitus (T2DM), may be a potential drug benefiting diabetic patients with SARS-CoV-2 infection, probably via a suppression of mTOR signaling together with its anti-inflammatory and anti-fibrosis function in lung. Remarkably, another kind of OADs, dipeptidyl Peptidase 4 (DPP4) inhibitor, may also exert beneficial effects in this respect, probably via a prevention of SARS-CoV-2 binding to cells. Thus, it is of significant to identify appropriate OADs for the treatment of diabetes in the context of SARS-CoV-2 infections.